Radiochemotherapy Versus Surgery in Nonmetastatic Anorectal Neuroendocrine Carcinoma: A Multicenter Study by the Association des Gastro-Entérologues Oncologues. Issue 42 (October 2015) - Brieau, Bertrand; Lepère, Céline; Walter, Thomas; Lecomte, Thierry; Guimbaud, Rosine; Manfredi, Sylvain; Tougeron, David; Desseigne, Françoise; Lourenco, Nelson; Afchain, Pauline; El Hajbi, Farid; Terris, Benoit; et al.
Abstract : Abstract: Neuroendocrine carcinomas (NEC) of the anus or the rectum are a rare disease, accounting for less than 1% of all digestive malignancies. Most are metastatic at diagnosis and treated with a platinum-based chemotherapy. No guidelines for localized tumors exist. The purpose of this study was to describe the characteristics of anorectal localized NEC, their management and their outcomes. We retrospectively reviewed patients from 11 French centers with anorectal localized NEC. We compared 2 therapeutic managements: surgery (group A) versus chemotherapy with or without radiation (group B). Progression-free survival (PFS) and overall survival (OS) were estimated with the Kaplan–Meier method. A total of 24 patients were identified with a median follow-up of 25 months (3–60 months). Median age was 63 years old and 17 had a rectal tumor (71%). Mean Ki-67 was 72% (range: 20–100), and 75% of the tumors had a high proliferative index (Ki-67 > 50%). Global PFS and OS were 13.1 and 44.1 months, respectively. Thirty-seven percent of patients were in group A and 63% in group B. There was no difference between group A and group B, whether in terms of PFS (13.0 months vs. 13.2 months, P = 0.75) or OS (49.1 months vs. 39.2 months, P = 0.42). In patients with anorectal localized NEC, chemotherapy with or without radiation obtained a similar outcome as surgery and this conservative approach could be deemed a reasonable option.